EXPERIENCES AND SATISFACTION WITH HEALTH CARE OF THE PATIENTS WITH NON-COMMUNICABLE DISEASES FROM URBAN AND RURAL AREAS IN PELAGONIAN AND SOUTHWESTERN REGION OF THE REPUBLIC OF NORTH MACEDONIA - Popovska Kljuseva, Svetlana; Stefanovska, Vesna Velikj; Kochinski, Dragan (Journal of Morphological Sciences; Vol 7 No 1 (2024): JMS, 2024)
Noncommunicable diseases (NCDs) are responsible for 41 million of premature lost lifeâ€™s each year, equivalent to 74% of all deaths globally. The experiences and satisfaction of patients with NCDs with the health care services are important indicator for measuring the quality in health care.  The aim was to perceive the experiences and satisfaction with health care of the patients with NCDs from urban and rural areas in Pelagonian and Southwestern region of the Republic of North Macedonia. This was a cross-sectional study conducted in the period 2023/24. A questionnaire derived from existing literature was used to measure the experience and level of satisfaction when receiving care. Patients with heart attack, strocke, cancer, chronic obstructive pulmonary disease, asthma and/or diabetes mellitus were included. About 192 patients were elaborated, 55.2% from urban and 44.8% from rural areas. Distance as a problem for an examination by a specialist was 3,25 times more common in rural areas. There was no significant association of practicing inappropriate attitude/behavior (p=0.259), denying the needs (p=0.495), language problem (p=0.089) and/or refusing treatment (p=0.854) by health personnel with the patient's place of residence. There was no significant association between the patients' from rural/urban areas and their experience for health status awareness (p=0.2252), confidentiality (p=0.1351), information consent (p=0.5439), access to medical documentation (p=0.0701), quality of care (p=0.1337) and safety (p=0.1315). The positive experience towards awareness of the health status significantly increased with the age of the patients - R (183) =0.167; p=0.023.  The patients from rural areas were significantly more satisfied with the consultationâ€™ time with the family doctor (p=0,0102). We belive that this study results may be useful for the policymakers when developing suitable strategies for safe and high-quality care for NCD patients. Keywords: experiences, satisfaction, health care, non-communicable diseases.